What Do You Want to Be? : Youth Aspirations in the Time of the COVID-19 Crisis - Evidence from Three Sub-Saharan Countries - Costa, Valentina; Contreras Gonzalez, Ivette Maria; Palacios-Lopez, Amparo (World Bank, Washington, DC, 2022)
Understanding the aspirations and goals of the youth is essential to developing effective employment policies. Policies should be designed to allow educational and professional aspirations of young people to align with pathways to achieving them. The data collected is nationally representative and age distribution is similar across countries. Recent surveys on youth or sub-populations of youth have included questions to capture career aspirations and life goals in the time of the Coronavirus (COVID-19) crisis. Incorporating the youth aspirations and employment module for High Frequency Phone Surveys (HFPS) into multi-topic household surveys has several advantages. In conclusion, measuring youth aspirations helps shed light on the possible employment outcomes that can be observed in adulthood and play a role in breaking poverty circles, which is highly relevant for public policy.